Islam Konservatif dan Masalah Kenegaraan - Feri Riski Dinata; Ali Kuswadi (TAFAHUS: JURNAL PENGKAJIAN ISLAM, 2021)
This article will discuss several discussion topics related to Conservative Islam and state issues. The research method used is descriptive-historical, which describes what happened in the past, and Analytical-Evaluative in dissecting the writings of Ahmad Syafi'i Ma'arif in his book Islam and State Problems, namely the emergence of the root problems of Islamic politics in Indonesia began during a period of political schism that occurred during the revolutionary period, where Islamic organizations separated from Masjumi, causing the weakening of the political power of the Muslim Ummah in Indonesia. As for Syafi’i Ma’arif's view of the debate that took place in the Constituent Assembly, he was openly grateful that the efforts of Islamic figures who wanted to make Islam the basis of the Indonesian state failed to materialize. So what will happen is great difficulty to implement it in the modern era, because all of this is the result of their ijtihad long before the fall of the Baghdad caliphate and he affirms his stance that efforts to turn Indonesia into an Islamic state, even if it is legal according to the Constitution in 1999 1950 was an unrealistic premature attempt because a solid religious intellectual foundation for such a building had not yet been created